Die Design Of A Transmitting Transistor In A 175 MHz Power Amplifier At 28V - Rajah, Prakash; Ismail, Razali; Rajah, Avinash (IEEE, 2004)
This paper presents the die design of a NPN transistor, which is targeted for operation in a power amplifier. The proposed die is designed using epitaxial planar bipolar junction technology. The transistor die is designed for operation in the 175MHz frequency range with a 28V biasing. It is capable of producing a maximum output power of 4W. It can be utilized in Class A, Class B or Class C power amplifiers meant for transmission purposes such as in mobile communication, industrial communication or military transmitters. The power amplifier is typically placed before the antenna in transmitter systems. It is best to couple the design in a two-stage amplifier to produce a significantly higher-powered signal for transmission.